Increased tolerance of Anopheles gambiae s.s. to chemical insecticides after exposure to agrochemical mixture - Nkya, Theresia E.; Mosha, Franklin W.; Magesa, Stephen M.; Kisinza, William N. (Tanzania Journal of Health Research, 2014)
Resistance of mosquitoes to insecticides is mainly attributed to their adaptation to insecticide-based vector control interventions. Although pesticides used in agriculture have been frequently mentioned as an additional force driving the selection of resistance, only a few studies were dedicated to validate this hypothesis. The objective of this study was to investigate the effect of exposure of the malaria mosquito, Anopheles gambiae s.s. larvae for 72h to sub-lethal concentrations of the agrochemical mixture (pesticides, herbicides and fungicides). Their subsequent tolerances were measured to deltamethrin (pyrethroid), DDT (organochlorine) and bendiocarb (carbamate) currently used for vector control. The mean LC50 was determined and tolerance ratios for larvae exposed to agrochemical comparatively with unexposed larvae were calculated and expressed as fold increased tolerance. Bioassays revealed a significant increase in larval tolerance to detamethrin (1.83-2.86 fold), DDT (1.31-1.53 fold) and bendiocarb (1.14-1.19 fold) following exposure to 0.1 µM and 1µM agrochemical mixture. The observed increased tolerance in this study is likely to be based on metabolic resistance mechanisms. Overall, this study reveals the potential of agrochemicals to increase the tolerance of mosquito larvae to chemical insecticides.